PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) PADA POKOK BAHASAN USAHA DI SMA ANJONGAN - Varastica, Dini; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The purpose of this research to improved physics result learning on the subject of besiness to the Tenth grade students of SMA Negeri 1 Anjongan was used to Contextual Teaching And Learning (CTL) model. From of this research was pre-experimental in the from one-group pretest-post test design. This technique was used simple random sampling which consist 30 students. The technique of data collection were observation technique and measurement by measuring tools in from of the result of leaning test. The result of Wilcoxon test showed there was an increase in students learning result with  was obtained Sig p of . It showed that the treatment CTL was effective to improved students learning result. The level of effectiveness obtained was included in the high category was 1,72.Kata kunci:Contextual Teaching And Learning Model, Learning Outcomes, Business